2022
DOI: 10.1021/acsami.2c14808
|View full text |Cite
|
Sign up to set email alerts
|

Beetle-Inspired Dual-Directional Janus Pumps with Interfacial Asymmetric Wettability for Enhancing Fog Harvesting

Abstract: Fog-harvesting devices (FHDs) have been widely explored and applied to alleviate the shortage of fresh water. However, during the fog collection process, how to maintain a balance between fog capture and water removal behaviors to enhance the water collection rate still remains a challenge. Herein, inspired by the Stenocara beetle, we combined a beetle-like Janus surface and the conventional cross-sectional Janus structure together, developed a simple spray-and-dry strategy to obtain three types of biomimetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…At 532.4 eV, there was a typical metal‐oxygen bond (Ni/Co─O), and at 533 eV, there was a carbonyl group. [ 13 ] These findings indicated that the stearic acid anion was attached to the surface of the cobalt‐nickel hydroxide via metal‐oxygen bonds, giving the fabric hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
“…At 532.4 eV, there was a typical metal‐oxygen bond (Ni/Co─O), and at 533 eV, there was a carbonyl group. [ 13 ] These findings indicated that the stearic acid anion was attached to the surface of the cobalt‐nickel hydroxide via metal‐oxygen bonds, giving the fabric hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by lotus leaves and beetles, Li's group developed a hydrophilic-hydrophobic/superhydrophilic unpaired lattice with a Janus structure for directional water transport. 144 Their test results showed that this HS (with alternating hydrophilic and hydrophobic surfaces and different wettability on both sides) can achieve a balance between fog capture and fog removal efficiency, and the maximum FC efficiency was measured to be 2478.73 mg m À2 h À1 .…”
Section: Dual Biomimetic Designmentioning
confidence: 99%
“…The name Janus membrane is derived from the ''two-faced god'' in ancient Roman mythology. 121,128,129 This design was inspired by the difference in wettability between the two sides of the lotus leaf. One of the most important properties of these membranes is their ability to manipulate and control fluid transport.…”
Section: The Development Of Fog Collection With Hierarchically Struct...mentioning
confidence: 99%
“…(b) Surface nonuniformity in the hydrophobic layer causes unidirectional transport. Reproduced from ref . Copyright 2022, American Chemical Society.…”
Section: Mechanisms Of Unidirectional Transportmentioning
confidence: 99%